The The Impact of Financial Development on Environmental Pollution in Asian Countries: Examining the Role of Corruption Control - Dang, Anh (International Journal of Energy Economics and Policy, 2025)
This study aims to assess the role of corruption control in the impact of financial development on environmental pollution in Asian countries from 2002 to 2022. Using the GMM model, the research results indicate that financial development has an inverse effect on environmental pollution, meaning that financial development contributes to improving environmental quality in the Asian region. Furthermore, the study also uncovers a non-linear relationship between these two variables, suggesting that the impact of financial development on the environment may change across different stages of development. Another important highlight of the study is the role of corruption control. The study employs the DID method to show that in countries with effective corruption control systems and high levels of comprehensive financial development, the positive impact of finance on the environment is more pronounced. This indicates that establishing a transparent and efficient business environment is crucial for maximizing the benefits of financial development in protecting the environment.